Analysis on Influences of Intra-Couplings in a MISO Magnetic Beamforming Wireless Power Transfer System - Kyungtae Kim; Han-Joon Kim; Dong-Wook Seo; Ji-Woong Choi (Energies, 2021)
Magnetic beamforming techniques can enhance the power transfer efficiency using focused magnetic fields by the multiple transmitters to the receivers. However, the intra-couplings that cause power leakage and phase distortion among the arrayed coils inevitably occur due to the deployment of coils having strong couplings between each other. Here, we analyze the adverse influences of intra-couplings and present the advantages of magnetically independent transmitters for multiple-inputs and single-output (MISO) WPT. The independent coil array can achieve focused magnetic fields by simply adjusting the amplitude of the transmitter voltage source without phase adjustment. The system also can eliminate the reactive power with the independent coil array to efficiently use the supplying power from the source. The analytical studies are verified by numerical and circuit simulation and experiments. Our analysis can be generalized to the MISO-WPT with an arbitrary number of transmitters. It can provide insight into designing and implementing the MISO-WPT applying magnetic beamforming.